Rancang Bangun Mesin Pemecah Biji Jagung Terhadap Kesesuaian Ukuran Partikel Butiran Untuk Bahan Baku Pakan Unggas - Mukhsin Anami; Indah Widanarti (Faculty of Agriculture, Musamus University, 2020)
ABSTRACT The aim of this research is design a machine for corn sheller which the results canbe used as raw material for animal feed, especially poultry. The results of thedesign the corn shellerusing a power drive motor AC electric one phase 3/4 Hp. The main components of the engine used are frames, hoppers, crushing chambers,filters, output lines, shafts and bearings. Based on the results of the machine worktest, the engine capacity is 13.13 kg / hour with the results of the analysis ofgranules held by mesh 10 is 70.56%, retained by mesh 18 is 13.20% and passmesh sieve is 16.24%. The material used in this study was dry corn grains with amoisture content of 10.5%. The resulting particle grain size is 2 mm, 1 mm and inthe form granules smooth, the granules are already very good for poultry feed rawmaterials. The results of the economic analysis of the machine designed wereobtained that the cost needed to break 1 kg of dry corn grains was Rp. 2361.